Correlation of Clinical, Radiological and Histopathological Pattern of Bronchial Carcinoma (Journal of Dhaka National Medical College & Hospital, 2023)
Background: Lung cancer was the most commonly diagnosed cancer as well as the leading cause of cancer death in males in 2008 globally Lung cancer is one of the most deadly tumours known. It is accurately found by many radiographic testing methods occasionally initiated for an unrelated silment. In light of new histology guided therapeutic modalities and lung cancer genetic categorization, histological characterisation of lung cancer has risen in prominence. The study was carried out to evaluate the correlation of clinical, radiological and histopatholgicalpattern of bronchial carcinoma.Methods: This observational cross sectional study was carried out in the Department of Medicine (Respiratory wing) Bangabandhu Sheikh Mujib Medical University (BSMMU) and National Institute of Chest Disease (NIDCH) during the period of September 2011 to February 2012. A total of 60 admitted patients with a clinical, radiological and histological diagnosis of bronchial carcinoma were enrolled in the study. Complete sociodemographic characteristics, smoking status, radiological, and histopathological characteristics of the tumor were recorded in the study. CT scan of the chest was done in the majority of the patient. CT-guided FNAC and US guided FNAC tissue sampling from lung lesions followed by histopathological examination was done to diagnose the appropriate tumor type. After collecting the data, the statistical analyses were performed using the licensed version of Statistical Package for the Social Science Version 23 (SPSS-23). The p value